ANALISA PENGARUH PENILAIAN PASIEN ATAS DIMENSI KUALITAS JASA TERHADAP CITRA RAWAT INAP (KELAS I, II, III) RUMAH SAKIT UMUM HAJI SURABAYA - Retnaningsih, Wiwik (Program Doktor Ilmu Ekonomi, 2009)
This research intends to recognize Service Quality Dimension implemented by RSU Haji Surabaya on Image of RSU Haji Surabaya . Analysis unit taken in this research are patients who using Stay-In Service (class I, II, III). Independent variables used in this research are Service Quality Dimension variable adapted from Charles W. Lamb, Joseph F. Hair, Carl are tangibles, empathy, assurance, responsiveness, reliability (2001:208). While dependent variable used Stay-In Service Image (Class I, II, III) RSU Haji Surabaya adapted from Philip Kotler statement (1997:208) comprise set of convince, idea, and impression owned by one against an object. Instrument used to helping data analysis are SPSS Version 11 for Windows. While analysis technique used is Multiple Linear Regression analysis technique get along with correlation coefficient analysis with F-test and t-test. Base on result of the analysis above, obtained simultaneous determination coefficient value or Adjusted RSquare around 0,524 which give mean that independent variable effect on Stay-In Service Image (Class I, II, III) variables changes of RSU Haji Surabaya are 52,4%. Correlation coefficient value ® 85,1% or approaching one mean there is significant value between independent variable against dependent variable are very relevant and positive (either simultaneous determination coefficient or correlation coefficient). Value Fcalculation namely 13.346 larger than value Ftable 2.31 then can be stated that independent variable simultaneously have effect on dependent variable that is Stay-In Service Image (Class I, II, III) of RSU Haji Surabaya . Ground on value of tcalculation gained from each independent variables are X1 = 2.108, X2 = 3.306, X3 = 1.056, X4 = 4.519, and X5 = 2.156, overall larger than value of ttable = 1.6609 with a = 5% then can be stated that respective independent variable partially have effect on dependent variable that is Stay-In Service Image (Class I, II, III) of RSU Haji Surabaya . Reliability variable as independent variable have biggest value among four independent variables = 11, 245. While multiple area test using there are nothing independent variable which have most dominant on Stay-In Service Image (Class I, II, III) of RSU Haji Surabaya . Keywords : patient assessment, service quality dimension and stay-in service image